Protection of Oxidative Stress-induced DNA Damage and Apoptosis by Rosmarinic Acid in Murine Myoblast C2C12 Cells - Jeong, Moon-Jin; Lim, Do-Seon; Kim, Sung Ok; Park, Cheol; Leem, Sun-Hee; Lee, Hyesook; Kim, Gi-Yung; Jeong, Soon-Jeong; Choi, Yung Hyun (Biotechnology and bioprocess engineering, 2022)
Rosmarinic acid (RA) is a naturally occurring polyphenolic compound that has been applied as a therapeutic antioxidant. However, its action mechanism in muscle cells remains unclear. The objective of the current study was to explore the protective effect of RA against DNA damage and apoptotic cell death caused by hydrogen peroxide (H 2 O 2 ) in mouse C2C12 myoblast cells and clarify related signaling pathway. Our results showed that pretreatment with RA significantly improved cell viability, inhibited apoptosis, and suppressed the generation of reactive oxygen species (ROS) in H 2 O 2 -treated C2C12 cells. Additionally, DNA damage triggered by H 2 O 2 was abrogated by RA pretreatment. Moreover, H 2 O 2 -induced mitochondrial dysfunctions associated with apoptotic events, including loss of mitochondrial membrane potential and adenosine triphosphate content, up-regulation of Bax, down-regulation of Bcl-2, and cytosolic release of cytochrome c , were reduced in the presence of RA. RA also attenuated H 2 O 2 -induced activation of caspase-9 and caspase-3, which was associated with the ability of RA to block the degradation of poly (ADP-ribose) polymerase. Furthermore, RA dramatically promoted nuclear translocation of nuclear factor erythroid 2-related factor 2 (Nrf2) and its phosphorylation in the presence of H 2 O 2 with concomitant upregulation of heme oxygenase-1 (HO-1) expression, a major downstream factor of Nrf2. Taken together, these results suggest that RA could protect C2C12 myoblasts from H 2 O 2 -induced damage by maintaining mitochondrial function while eliminating ROS along with activation of the Nrf2/HO-1 antioxidant pathway, indicating that RA may be a potential therapeutic candidate to treat oxidative stress-mediated injury.